Shrinking Agricultural Land and Changing Livelihoods After Land Acquisition in Vietnam - Tuan, Nguyen Tran (Bulletin of Geography. Socio-economic Series, 2021)
The phenomenon of agricultural land shrinking is widespread in the world. This phenomenon stems from many reasons, and industrialization is one of those reasons. To perform the industrialization process, land acquisition is a tool used in most countries to convert land use from agriculture to non-agriculture. This paper survey 100 land-lost households to examine the impact of farmland shrinking on their livelihoods in Vietnam. The study focuses on three factors related to employment and income, how to use compensation money, and quality of life after land loss. The results show that the revenue increased by 1,500 USD per household compared to before. The rate of the employed population depends on age and gender. Workers over 35 for women and 40 for men showed an increase in unemployment. The use of compensation money focuses on non-farm goals, with the bright spot being an investment in education for future generations. The environment and society tend to worsen, but households’ last choice is to enjoy life after land acquisition.